2001
DOI: 10.1097/00130478-200110000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The use of a mobile computed tomography scanner in the pediatric intensive care unit to evaluate airway stenting and lung volumes with varying levels of positive end-expiratory pressure

Abstract: Mobile CT scanners can be used in the PICU for the diagnostic evaluation of critically ill children. This option allows for the continuation of medical therapies and monitoring in the intensive care setting while avoiding the potential complications of transporting a critically ill child to the radiology department. The use of mobile CT scanners may disrupt PICU routine and is more expensive than use of fixed CT scanners. Mobile CT scanners may be useful in radiographically determining the optimal level of PEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…PCT has been used quite extensively in adult neurosurgery as well as adult intensive care for over a decade [10,11] to overcome the potential risks with transferring patients to the RD. However, in the pediatric age group, PCT is rarely described, with reported use during neurosurgical operations [12] and within the PIC setting for the evaluation of airway [13]. There is no available literature on the use of PCT in neurocritical children.…”
Section: Discussionmentioning
confidence: 99%
“…PCT has been used quite extensively in adult neurosurgery as well as adult intensive care for over a decade [10,11] to overcome the potential risks with transferring patients to the RD. However, in the pediatric age group, PCT is rarely described, with reported use during neurosurgical operations [12] and within the PIC setting for the evaluation of airway [13]. There is no available literature on the use of PCT in neurocritical children.…”
Section: Discussionmentioning
confidence: 99%
“…large equipment) and radiation exposure of patients. Hertzog et al have reported a case study using mobile CT scanners to optimize PEEP in a 6-month-old premature infant (Hertzog et al, 2001). However, even with the development of low-dose CT, radiation exposure makes it practically impossible to use CT to guide PEEP titration at the bedside.…”
Section: Optimizing Peep With Imaging Techniquesmentioning
confidence: 99%
“…However, Burke found that such 'virtual endoscopy' was not as sensitive as actual endoscopy in detecting dynamic airway obstruction [28]. Hertzog, in a single case report in a patient with airway malacia describe the use of CT technology in the ICU setting to determine the ventilatory settings for optimum lung volumes, with minimal disruption of patient care [29].…”
Section: Accurate Physiologic and Anatomic Diagnosismentioning
confidence: 99%